Sistem Informasi Penggajian Pegawai Kecamatan Geneng Kabupaten Ngawi - Setyawan, Arif; Wandyatmono, Joko; Susanti, Veronika (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
District of Geneng of Sub-Province Ngawi consists of eighteen countryside. Apart the countryside governance with the sub-province about ten kilo meters. This area has temperature of between 260 C- 360 C. Wide of region of District Geneng 87.04 km2 with amount resident 89.663 head. Resident living in region of District Geneng most is farmer. Office of Governance of District Geneng occupies the farm of property of government for the width of 1.919 m2 broadly building 1.204 m2. District officer of counted 27 people, consisted of the faction III are nine people, faction II are three of compassion of people and faction I of[is five of people. Writer perform research in District Geneng as a mean to deepen farther about remuneration service and also wish to know the problems that happened [in] the institution, besides also aim to fulfill some of pass conditions which have been specified by University Surakarta. Having taken steps of Research hence writer can find the problem faced by the institution that is about difficulty in tracing identity of officer and difficulty in searching remuneration data. Therefore writer design the information system employ the officer to overcome the problem. Research method which writer use method of book studies, observation, interview and analyzes. This report is limit at scheme of information system remuneration covering: making DFD, database scheme, flowchart and input scheme and also output. System scheme aim to facilitate in application making in fact. After perceiving scheme of information system which have been made by a writer can take the conclusion that with the existence of system scheme, hence application making which in fact will easy to executed. As for database designed is officer database, database of remuneration and intake database employ. Hereinafter using Visual Basic or Visual Foxpro can use scheme of information system of remuneration in District Geneng in making of Remuneration application in District of Geneng of Sub-Province Ngawi.